The Challenge to the South: Independent Commission of the South on Development Issues - Independent Commission of the South on Development Issues; Independent Commission of the South on Development Issues (New York : Oxford University Press, 1990)
"The struggle to overcome poverty and improve the quality of life for the three fourths of humanity living in the developing countries--the South--is the subject of this report by a high-level, independent group, from different backgrounds and political persuasions, from the South itself. It examines the South's development record, assesses the achievements, analyses the failings, and suggests direction for reform. Book jacket."--BOOK JACKET
Includes bibliographical references and index.
eng
Keywords: Democracy; Developing countries economic; International cooperation